(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Plants have been the main source of therapeutic agents in world’s most ancient system of medicine, the Ayurveda. Nimb (also known as Margosa tree) is one of the most commonly used plants in Ayurveda for the management of a large number of ailments. It is a member of the Meliaceae family, found commonly in India, Africa and America. Nimb has been used exclusively by mankind to treat various diseases since even before the availability of manuscripts that recorded the beginning of history. Nimb is well described in Charak Samhita, Sushrut Samhita, Ashtang Hridayam, Chikitsa grantha and Nighantus. It is having Laghu guna, Tikta kashaya rasa, Sheeta virya and Katu vipaka, due to which it has been considered as Kapha-pitta shamaka. Acharya Bhav Mishra considers it Tridosh Shamak. It is traditionally used in the treatment of various ailment i.e., Krimi, Kushtha, Jwara, Kandu, Shopha and many more. All the parts of the plant have been used in the preparation of therapeutic formulations. Nimb contains various bioactive compounds like Nimbinin and Nimbidin, due to which it shows antibiotic, antiulcer, anti-inflammatory, antihelmenthic, antifungal, diuretic, antihistaminic, nematicidal and spermicidal properties and other biological activities. Present paper is an effort to validate pharmacological properties of Nimb described in Ayurveda through reverse pharmacology.